Strategi Guru Dalam Pelaksanaan Tata Tertib Sekolah di Kelas III SDN 3 Sigar Penjalin Tahun Ajaran 2023/2024 - Ningsih, Decha Rosiana; Alawiyah, Tuti; Hafizin, Muhammad (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
This research is to describe teachers' strategies in implementing school rules and regulations in class III at SDN 3 Sigar Penjalin for the 2023/2024 academic year. The method used in this research is a qualitative approach in terms of the method is a descriptive method. Data collection techniques use observation, interviews and documentation techniques. The data sources for this research are school principals, teachers and students. And the data analysis techniques used in this research are data collection, data reduction, presentation and drawing conclusions. The results of the research show: (1) Implementation of school rules in class III at SDN 3 Sigar Penjalin. The results of research conducted by researchers at SDN 3 Sigar Penjalin show that the implementation of school rules at SDN 3 Sigar Penjalin is still said to be not going well. Because there are still some students who do not obey and carry out school rules properly. There are still some students who violate the rules that have been made by the school. For example, arriving late and not wearing full uniform attributes during the flag ceremony. (2) Factors that cause violations of discipline in class III of SDN 3 Sigar Penjalin. Environmental factors are the main points that influence children's lack of discipline in learning. However, building an environment that cares about education is not an easy job. Parents of students who have never received education will find it difficult to determine methods or educate their children with the right approach. On the other hand, a good environment that cares about education demands learning support facilities such as access to book technology and other learning facilities and meeting these needs requires a budget. (3) The impact of implementing the Rules of Conduct on class III students at SDN 3 Sigar Penjalin. The existence of these school rules can have a good impact on students, teachers, and the surrounding community, such as students becoming disciplined, students not liking to miss classes, and students no longer being noisy. In class during KBM, students don't want to make mistakes again because they are afraid of the punishment given by the teacher.